Cost-effectiveness of childhood influenza vaccination in Europe: results from a systematic review. (3rd September 2021) - Boccalini, Sara; Bechini, Angela; Moscadelli, Andrea; Paoli, Sonia; Schirripa, Annamaria; Bonanni, Paolo
ABSTRACT: Introduction : Influenza can be a significant public health problem. Nevertheless, it is preventable through vaccination. Concerning the pediatric population, the recommendation of influenza vaccination is under-represented in many European countries. The aim of this systematic review is to evaluate the cost-effectiveness of universal childhood vaccination against influenza in Europe. Areas covered : We conducted a systematic review of original article assessing the cost-effectiveness of influenza vaccination by searching PubMed, Embase and Scopus databases for studies in English, starting from January 1 st, 2010 up to October 21 st, 2020. Expert opinion : Our literature review showed that all studies identified highlight that pediatric vaccinations using a live vaccine, especially in the quadrivalent formulation, are cost-effective compared to current vaccinations (elderly and at-risk groups) with TIV or no vaccination. A significant contribution to this positive economic profile is due to the indirect protection. Already many clinical data report the relevant direct and indirect impact of vaccination against influenza for younger subjects. The recent studies collected in this review showed also that the pediatric vaccination is also cost-effective. Therefore, decision-makers should now consider this new favorable evidence.